Yolks color definition by supplementing yellow and red xanthophylls to hen's diets - Ponsano, Elisa Helena Giglio [UNESP]; Sandeski, Ligia Mara [UNESP]; Grassi, Thiago Luís Magnani [UNESP]; Garcia Neto, Manoel [UNESP]; Pinto, Marcos Franke [UNESP] (My University, 2014)
Egg yolk color may be controlled both by the concentration and the type of xanthophylls added to diets, with the aim of meeting consumers demand. The objectives of this work were to study how yellow and red xanthophylls present in laying hens` diets influence yolks colors and find the concentrations of these ingredients that meet the regional consumer desire. A factorial design 5 x 3 with 5 concentrations of yellow xanthophylls (lutein + zeaxantin 40%; 1.0, 1.25, 1.5, 1.75 and 2.0 mg/hen/d) and 3 concentrations of red xanthophylls (canthaxantin 10%; 0, 0.35, 0.7 mg/hen/d) was used. After a 30 d period receiving corn basal diets and water ad libitum, 60 White Dekalbe hens were distributed to receive the 15 dietary treatments in 4 replicates. Diets were provided daily at 110 g, during 21 d under 16 h light/8 h dark. Yolks colors were evaluated daily using the CIE L, a, b color space and the Roche color index. After the color stabilization, data were analyzed by ANOVA, regression analysis and Response Surface Methodology (MRS). Global acceptance for the Roche colors was evaluated with a 5 points hedonic scale and data were analyzed by Friedman and Dunn tests. Significance was established at 95% (P < 0.05). Regression analysis showed that the red xanthophylls content was the most important factor that defined L, a and b values for yolk color (P < 0.0001; square function), although its effect was significantly affected by the yellow xanthophylls contents (P = 0.0277; P < 0.0001; P = 0.0002 for L, a, b, respectively), providing evidence for a synergistic effect and not for a saturation effect. MRS showed that the highest redness of yolks was reached with 1.5 mg/hen/d of yellow and 0.5 mg/hen/d of red xanthophylls. So, higher supplementations aiming at increasing yolk color would bring an unnecessary cost to the ration. The most accepted yolk color scored 9, which corresponded to mean color attributes L = 65; a = 16; and b = 64. MRS showed that these values could be reached with combinations of yellow:red xanthophylls like 1.0:0.15 or 1.5:0.1 mg/ hen/d or simply with the yellow xanthophylls at 2.0 mg/hen/d. So, it was concluded that both yellow and red xanthophylls are important to define yolks color; that high amounts of xanthophylls are unnecessary to bring changes to color; and that Brazilian consumer requires yolks color attainable with few amounts of red xanthophylls or only with the yellow ones.
Yolks color definition by supplementing yellow and red xanthophylls to hen's diets
Keywords: Lutein; Zeaxanthin; Canthaxanthin; Corn; Response surface methodology